2007
DOI: 10.1080/00016340600855763
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome of uterine arterial embolization followed by selective hysteroscopic removal of a placental polyp

Abstract: Selective removal directed via hysteroscopy after reduction of blood supply by uterine arterial embolization provides a safe and effective method to minimize bleeding, and can preserve future fertility and successful uneventful pregnancies in the treatment of placental polyp with abundant blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In order to preserve the uterus, transcervical hysteroscopic resection (TCR) was performed whenever possible. Despite reports related to the usefulness of uterine artery embolization (UAE), we did not perform UAE in our cases to avoid possible adverse effects on normal myometrium and ovarian function . With the speculation in mind that waiting a longer period until surgery may reduce intra‐polyp blood flow, the resection procedure was delayed as long as possible in cases showing imaging evidence of increased blood flow within the myometrium/placental polyp, in an attempt to reduce blood loss during surgery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to preserve the uterus, transcervical hysteroscopic resection (TCR) was performed whenever possible. Despite reports related to the usefulness of uterine artery embolization (UAE), we did not perform UAE in our cases to avoid possible adverse effects on normal myometrium and ovarian function . With the speculation in mind that waiting a longer period until surgery may reduce intra‐polyp blood flow, the resection procedure was delayed as long as possible in cases showing imaging evidence of increased blood flow within the myometrium/placental polyp, in an attempt to reduce blood loss during surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, placental polyp removal surgery and uterine artery embolization have been proposed as surgical methods with the intention to preserve the uterus, and in some cases, a combination of these procedures has been chosen as a treatment method …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Dyer I et al in their retrospective study concluded that after precise evaluation of neovascularization by computed tomographic angiography, hysteroscopic resection with preoperative uterine artery embolization is an effective minimally invasive procedure to conservatively treat placental polyp with prominent neovascularization. 22 Jimenez JS et al in their study concluded that diagnosticoperative ambulatory hysteroscopy is a suitable alternative to blind curettage in the management of retained trophoblastic tissue.…”
Section: Managementmentioning
confidence: 99%
“…Placental polyp is a polypoid mass in the uterine cavity which is a fragment of placental tissue retained for an indefinite period after abortion or parturition (1)(2)(3). It is a potentially life-threatening condition that, in extreme cases, may require hysterectomy.…”
mentioning
confidence: 99%